Efeito agudo de alongamentos com torque e ângulo constantes na amplitude de movimento, propriedades passivas musculares e na percepçãode desconforto ao alongamento - Christian Emmanuel Torres Cabido (2012)
The comparison between the effects of stretching exercises with constant torque (CT) and constant angle (CA) has been scarcely investigated. The aim of the present study was to compare the acute effect of stretching exercises CT and CA on maximum range of motion (ROMmax), resistance torque for a fixed range of motion (RT_), stiffness, energy and range of motion and resistance torque corresponding to the first sensation of tightness in the posterior thigh (FSTROM and FSTRT, respectively). The study was approved by the Ethic Committee of Federal University of Minas Gerais in accordance with international standards (COEP 0610.0.203.000- 10). Twenty three sedentary men, between 19 and 33 years old, participated in the study. All subjects underwent one familiarization session and then proceeded randomly to the stretching conditions CA or CT, respecting an interval of 48 to 72 hours between each session training. Measurements were performed at the right limb for training groups and the left limb was used as control (CON). An isokinetic dynamometer (Flexmachine) was utilized to analyze the hamstring muscles during a passive knee extension. ROMmax was operationally defined as the maximum tolerated stretch by the subject. Four sets of 30s of stretch (CA or CT) at 95% of ROMmax, and an interval of approximately 15s were performed. Data were analyzed as percentage difference between post and pre-test. An one way ANOVA with repeated measures followed by a paired Student's t test with Bonferroni correction was utilized. Significance level was set at _ = 0,05 and data are presented as mean ± standard error. ROMmax increase in CT (17,3 ± 1,4%) was higher than in CA (11,0 ± 1,0%) (p <0,01). RT_ decrease in CT (28,1 ± 2,4%) was similar to CA (20,5 ± 3,2%) (p = 0,06). Stiffness decrease in CT (25,5 ± 3,2%) was higher than in CA (17,5 ± 1,7%) (p <0,05). Energy decrease only in CT (28,2 ± 2,6%). FSTROM increase in CT (21,8 ± 3,7%) was similar to CA (17,8 ± 3,3%) (p = 0,42). For FSTRT, there were no differences between groups CT (9,0 ± 4,3%), CA (5,5 ± 4,4%) and CON (-1,4 ± 3,9%) (F = 1,75, p = 0,18). The CT stretch protocol increased ROMmax in a greater magnitude compared with CA stretch protocol, this may have been caused by greater changes in the MTU biomechanical properties, measured by stiffness and energy.